2014
DOI: 10.1007/s10162-014-0477-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Basilar Membrane Motion During Round Window Stimulation in Guinea Pigs

Abstract: Driving the cochlea in reverse via the round window membrane (RWM) is an alternative treatment option for the hearing rehabilitation of a nonfunctional or malformed middle ear. However, cochlear stimulation from the RWM side is not a normal sound transmission pathway. The basilar membrane (BM) motion elicited by mechanical stimulation of the RWM is unknown. In this study, the BM movement at the basal turn was investigated in both reverse via RWM drive and acoustic stimulation in the ear canal or forward drive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…The measurement of the stapes head in this study was recorded at a nearby site compared with the incus tip reported previously, both around the incudostapedial joint. The mean stapes head displacement of the control group in this study was in accordance with that reported by Guan and Gan [17] (Figure  4A in their paper) on the whole but was generally higher than that reported by Chen et al [23]. Murakami et al [21] reported that the stapes velocity decreased over 0.4–5.0 kHz in fresh human temporal bones with increased hydrostatic pressure of the inner ear under sound pressure of 114 dB SPL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The measurement of the stapes head in this study was recorded at a nearby site compared with the incus tip reported previously, both around the incudostapedial joint. The mean stapes head displacement of the control group in this study was in accordance with that reported by Guan and Gan [17] (Figure  4A in their paper) on the whole but was generally higher than that reported by Chen et al [23]. Murakami et al [21] reported that the stapes velocity decreased over 0.4–5.0 kHz in fresh human temporal bones with increased hydrostatic pressure of the inner ear under sound pressure of 114 dB SPL.…”
Section: Discussionsupporting
confidence: 91%
“…The displacement of the incus tip in guinea pigs under 80 dB SPL acoustic stimulation in the ear canal was reported by Guan and Gan [17] and by Chen et al [23]. The measurement of the stapes head in this study was recorded at a nearby site compared with the incus tip reported previously, both around the incudostapedial joint.…”
Section: Discussionsupporting
confidence: 57%
“…Colletti et al proved its beneficial outcome by placing the FMT on the RW . Recently, the basilar membrane response to forward and reverse stimulation was measured using an animal model, and the response was also similar in nature . Average hearing gain in stapes vibroplasty and RW vibroplasty, which is a forward and reverse stimulation, did not differ significantly in our study in accordance with the recent report.…”
Section: Discussionsupporting
confidence: 91%
“…They are also popular models for studies of middle (Guan and Gan, 2011; Lee et al, 2014) and inner (Chen et al, 2014) ear mechanics likely because the guinea pig is audiometrically similar to humans in that they hear sounds over comparable ranges of frequencies (Heffner et al, 1971; Syka et al, 2000). Guinea pigs also share similar pinna features (Greene et al, 2014) as humans–unlike many other commonly used animal models (i.e., cat, chinchilla, bat) with upright, conical pinna, guinea pigs have more oval-shaped, “flattened” ears positioned on either side of the head.…”
Section: Introductionmentioning
confidence: 99%